2022
DOI: 10.3390/ijms23042025
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression Pattern of FGFR1, FGFR2, RIP5, and HIP2 in Developing and Postnatal Kidneys of Dab1−/− (yotari) Mice

Abstract: This study aimed to explore how Dab1 gene functional silencing influences the spatial and temporal expression patterns of fibroblast growth factor receptor 1 (FGFR1), fibroblast growth factor receptor 2 (FGFR2), receptor-interacting protein kinase 5 (RIP5), and huntingtin-interacting protein 2 (HIP2) in the developing and postnatal kidneys of the yotari mice as potential determinants of normal kidney formation and function. Dab1−/− animal kidneys exhibit diminished FGFR1/FGFR2 expression in all examined develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…These malformations are the most common congenital disabilities and the leading cause of end-stage renal disease in children [ 38 , 39 ]. In our earlier research with yotari mice, we discovered a series of different markers and how disruption in one step of their signaling pathways can result in CAKUT [ 11 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…These malformations are the most common congenital disabilities and the leading cause of end-stage renal disease in children [ 38 , 39 ]. In our earlier research with yotari mice, we discovered a series of different markers and how disruption in one step of their signaling pathways can result in CAKUT [ 11 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, monogenic disorders related to CAKUT involve mutations in 23 genes and have been identified in a small percentage (12%) of examined cases, with insufficient evidence of their causative role [ 7 ]. This research aimed to investigate the spatio-temporal expression of RIP5 , a new CAKUT candidate [ 9 ], and FGFR1 , and FGFR2 , well-known potential candidate genes, in developing human kidneys and kidneys affected with congenital anomalies [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier studies on human kidneys showed RIP5 expression in early human kidney development from the 5th to 22nd dw, noticed first in the undifferentiated metanephric mesenchyme [ 12 ]. We found a notable membrane-associated distribution of RIP5 in mesenchymal-derived cells in mice kidney development (E15.5) [ 9 , 13 ]. We also showed RIP5, FGFR1, and FGFR2 expression patterns, which decreased during human kidney development from the 6th to the 22nd developmental week [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations